Thioether functional chain extender for thermoplastic polyurethanes - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2015)
In this study, a novel three functional chain extender (TATATRIOL) was synthesized from the reaction of 1,3,5-tri(prop-2-en-1-yl)-1,3,5-triazinane-2,4,6-trione (TATA) with 2-sulfanylethanol. Then new thermoplastic polyurethanes (TPUs) were synthesized by a one-step bulk polymerization from the reaction of 1,1'-methanediylbis(4-isocyanatocyclohexane) (H12MDI), a poly(ethylene adipate) based polyester polyol and a chain extender. Butane-1,4-diol (BD) and the newly synthesized monomer, TATATRIOL, were used as chain extenders. The effects of TATATRIOL on the properties of the TPU were investigated and compared to those of the TPU prepared with BD. The TPUs which derived from the sulfur containing chain extender displayed lower modulus and high elongation at break values than the analogous TPUs derived from BD. Moreover sulfur containing TPUs exhibited higher thermal stability.
Keywords: Elastomers; Thermogravimetric analysis (TGA); Differential scanning calorimetry (DSC); Polyurethanes; SEGMENTED POLYURETHANES; HDI; DEGRADATION; MORPHOLOGY; THIOL